VASCULAR ANATOMY CHARACTERISTICS OF THE PANCREATICODUODENAL REGION IN MULTIDETECTOR CT SCANNER IN BACH MAI HOSPITAL - Nguyễn , Thị Ngọc; Nguyễn , Khôi Việt; Vu, Đăng Lưu; Hoàng, Thị Vân Hoa; Trần, Đức Huy (Tạp chí Điện quang & Y học hạt nhân Việt Nam, 2024)
Objective: To describe vascular anatomy characteristics of the pancreaticoduodenal region in multidetector CT (MDCT) scanner in Bach Mai Hospital). Methods: Select good quality images among patients having abdominal MDCT in Bach Mai Hospital until 9/2023. Categorize these patients into different types of pancreaticoduodenal vascular anatomy. Calculate the number and percentage of those types. Results: Out of 431 selected cases: the rate of visualization for great vessels, the inferior pancreaticoduodenal artery (IPDA), first jejunal vein (FJV) was 100%, 77,9%, and 86,1% relatively. Replaced left hepatic artery (LHA) arising from the left gastric artery is the most common variant (10.4%), the second variant is replaced right hepatic artery (RHA) arising from the superior mesentery artery (SMA) (4.6%). IPDA has its common trunk that arose from the first jejunal artery (J1A), SMA, and two branches arose from different origins, in 59.2, 26.8, and 14% of cases, respectively. Meanwhile, IPDA has its origin on the dorsal, right, and left aspects of the SMA in 56.6, 23.5, and 19.9% respectively. The trajectory of the first jejunal trunk (FJT) related to the SMA was anterior in 24% of cases, posterior in 60.5% of, and first and second jejunal vein (J1V and J2V) with an anterior and posterior trajectory in 15.5% of cases. Conclusion: MDCT scanner enables visualization of small vessels in the pancreaticoduodenal region with high sensitivity.